Innovation Law and Policy and Business Model - Carvalho, Sônia Marise Salles; Aranha, Elzo Alves (Archives of Business Research, 2021)
The objective of the research is twofold: a) to explore the law innovation and policy (ILP) in connection with the business model (BM) seeking to identify the main elements; b) to structure a set of key aspects based on the elements identified in the connections between ILP and BM. Next, we intend to apply the key aspects proposed in a Brazilian federal public university. The research is exploratory, qualitative, based on a case study. The findingss obtained point to six key aspects: value as a unit of analysis, value segment, systemic perspective, alignment among dimensions, balance between supply and demand and new configuration pattern. The findings obtained are innovative and contribute to fill the gap in the academic literature of ILP and BM. The findings have three practical implications, for strategic leaders of higher education institution (HEI), coordinators and professors of HEI and the federal government.